Consumer Testing Data on Matooke generated by NARL & Bioversity in Uganda - Akankwasa, Kenneth; Marimo, Pricilla; Nowakunda, Kephas (2023)
This dataset contains data generated during the Activity 5 or Step 4 - Consumer Testing in Rural and Urban Areas performed by the NARL & Bioversity team in Uganda on Matooke, within the RTBfoods project (following the Methodological Guidance and its supplement).